Activation of the C–C Bond Using Brønsted Acid NaHSO4/SiO2: Synthesis of Triarylmethanes from 3-Benzhydryl Pentane-2,4-dione and Aromatic Compounds - Aoyama, Tadashi; Hayakawa, Mamiko; Ogawa, Sumire; Nakajima, Erika; Mitsuyama, Emi; Iwabuchi, Taku; Takido, Toshio; Kodomari, Mitsuo (Synlett, 2014)
A novel and efficient method for the activation of the C(sp3)–C(sp3) bond was developed. The C(sp3)–C(sp3) bond in 3-benzhydryl pentane-2,4-dione was easily cleaved in the presence of NaHSO4/SiO2 to form benzhydryl cation which reacted with aromatic compounds at 110 °C for five to six hours to afford triarylmethanes in good yields. This reaction using Brønsted acids was applicable for the alkylation of electron-rich aromatics containing alkyl halides as a side chain.
Keywords: C–C bond activation; C–C bond formation; solid acid; alkylation; heterogeneous reaction